Salmeterol and Airway Response to Allergen - Donald W Cockcroft; Veronica A Swystun; Rajesh Bhagat; Sanjay Kalra (Canadian Respiratory Journal)
BACKGROUND: Regular treatment with inhaled salbutamol (seven to 14 days) increases airway responsiveness to allergen.